Ni(OH)(2) nanosheets grown on porous hybrid g-C(3)N(4)/RGO network as high performance supercapacitor electrode - Li, Lei (Sci Rep, 2017)
A porous hybrid g-C(3)N(4)/RGO (CNRG) material has been fabricated through a facile hydrothermal process with the help of glucose molecules, and serves as an efficient immobilization substrate to support ultrathin Ni(OH)(2) nanosheets under an easy precipitation process. It was found that the g-C(3)N(4) flakes can uniformly coat on both sides of the RGO, forming sandwich-type composites with a hierarchical structure. It is worth noting that the introduction of the g-C(3)N(4) can effectively achieve the high dispersion and avoid the agglomeration of the nickel hydroxide, and significantly enhance the synthetically capacitive performance. Owning to this unique combination and structure, the CNRG/Ni(OH)(2) composite possesses large surface area with suitable pore size distribution, which can effectively accommodate the electrolyte ions migration and accelerate efficient electron transport. When used as electrode for supercapacitor, the hybrid material exhibits high supercapacitive performance, such as an admirable specific capacitance (1785 F/g at a current density of 2 A/g), desirable rate stability (retain 910 F/g at 20 A/g) and favorable cycling durability (maintaining 71.3% capacity after 5000 cycles at 3 A/g). Such desirable properties signify that the CNRG/Ni(OH)(2) composites can be a promising electrode material in the application of the supercapacitor.